Cloudland Revisited : a misspent youth in books and film - Perelman, S. J. (Sidney Joseph), 1904-1979 (Library of America, 2024)
"From October 1948 to October 1953, The New Yorker published humorist S. J. Perelman's "Cloudland Revisited" series: twenty-two reviews of once-popular books and silent films whose expiration dates had passed. All but forgotten even at the time, they were nonetheless part of Perelman's youth and made an indelible mark on him. ln the comic genius's biting satire they live once again: Gertrude Atherton's sensationalist fantasy Black Oxen; Sax Rohmer's supervillain blockbuster The Mystery of Dr. Fu-Manchu; the "underwater" silent film adaptation of Twenty Thousand Leagues under the Sea; Edgar Rice Burrough's 1914 novel Tarzan of the Apes; and George Barr McCutcheon's 1901 historical fantasy novel Graustark-the Game of Thrones of its era-which launched numerous sequels and film adaptations. Here for the first time all twenty-two of Perelman's reappraisals are collected. With self-deprecating humor and frequent embarrassment, Perelman reflects on how rereading and rewatching brings us in contact with how we, like an old book or film, have both changed and remained the same. This paperback includes a tribute to Perelman's art by another New Yorker favorite, Adam Gopnik"-- Provided by publisher.